KELAYAKAN BODY LOTION DARI ALPUKAT DAN KULIT SEMANGKA UNTUK PERAWATAN KULIT KERING - Hanif, Amelia; Astuti, Murni (Ensiklopedia of Journal, 2025)
Abstract: Many people often experience dry skin problems which cause rough and scaly skin, so skin care needs to be done to maintain skin moisture. For this reason, cosmetics are needed to maintain skin moisture, such as body lotion made from avocado and watermelon skin which contains vitamin C which is useful for moisturizing dry skin. This research aims to analyze the manufacture and feasibility of avocado and watermelon rind body lotion as assessed from laboratory tests, organoleptic tests and hedonic tests. This research uses an experimental method with a quantitative approach. Based on the results of this research, the vitamin C content level was 15.2472% per 10 grams. Meanwhile, the pH test results of the preparation were 4.9 and the resulting body lotion was homogeneous. From the results of the texture organoleptic test, 57% of the panelists said that the texture of the body lotion was quite smooth, 71% of the panelists said that the body lotion was light beige in the color organoleptic test, and 57% of the panelists said that the aroma organoleptic test of the body lotion had a soft scent. Meanwhile, from the hedonic test results, 57% of the panelists said they really liked the avocado and watermelon rind body lotion. Based on the research results, it can be concluded that avocado and watermelon skin body lotion has the function of moisturizing dry skin.Keywords: Feasibility, Avocado, Watermelon Rind, Body Lotion, Dry Skincare.